Improvement of Economical and Ecological Efficiency of Water Preparation Process - M. F. Jalilov; B. S. Badalov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains results of the investigations pertaining to specific volume and composition of neutral and acid portions of the used reclaiming solution of H-cationic filters used in a chemical desalting plant. The filters operate in accordance with small run-off technology and they are applied for regeneration of Na-cationic filter and acidification of limed water for replenishment of a heating system.